Correction Fluid

The correction fluid formulation with specific aspect ratio particles addresses the issue of hard cake formation in conventional correction fluids, ensuring uniform coating and effective concealment by maintaining titanium oxide dispersion over time.

JP7619031B2Active Publication Date: 2025-01-22PENTEL KK
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2020206280
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-11
Publication Date
2025-01-22
Estimated Expiration
2040-12-11

AI Technical Summary

Technical Problem

Conventional correction fluids using titanium oxide for concealing typographical errors face issues with redispersibility due to the formation of hard sedimentary layers, leading to insufficient concealment and uneven coating films upon repeated use.

Method used

A correction fluid formulation comprising specific aspect ratio particles such as dry silica, fatty acid amide, modified urea, polyethylene oxide, and bentonite, with hydroxyl groups on the surface, maintains titanium oxide in a dispersed state, preventing the formation of hard cakes and ensuring uniform coating even after prolonged use.

Benefits of technology

The formulation effectively maintains titanium oxide dispersion, preventing the formation of hard cakes and ensuring a uniform coating film, even after repeated stirring and long-term storage, thereby providing effective concealment of errors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007619031000011
    Figure 0007619031000011
  • Figure 0007619031000012
    Figure 0007619031000012
  • Figure 0007619031000013
    Figure 0007619031000013
Patent Text Reader

Abstract

To provide a correction liquid capable of forming an excellent coating film even after repetition of stirring, painting and standing for a long period.SOLUTION: A correction liquid comprises titanium oxide, a hydrocarbon solvent, a particle having a major axis of 1.6 μm or more and 170 μm or less, a minor axis of 0.1 μm or more and 1.3 μm or less, and an aspect ratio (major axis / minor axis) or 5 or more, a mixture including one or two or more selected from dry silica, fatty acid amide, modified urea, polyethylene oxide and bentonite, and a resin soluble in a hydrocarbon solvent.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a correction fluid that is applied to cover a typo or the like to conceal the typo and enable new characters or the like to be rewritten on top of it. [Background technology]

[0002] Conventionally, titanium oxide, which is known to have high concealing properties, has been widely used as a means of covering and concealing typos and other errors in corrections. Titanium oxide has a high specific gravity and is prone to settling, and the settled titanium oxide becomes a hard sedimentary layer called a hard cake over time, which cannot be redispersed by simply shaking the container. Therefore, correction fluid and marker ink that use titanium oxide require a metal or glass stirrer to be placed in the container and the container to be shaken before use to redisperse the settled titanium oxide. Patent Document 1 discloses a correction fluid that uses titanium oxide as a masking material and anhydrous silica obtained by a dry method to improve redispersibility. Furthermore, Patent Document 2 discloses a white ink that can also be used as a correction fluid, which uses needle-shaped particles to improve redispersibility. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2001-152097 A [Patent Document 2] JP 2012-131927 A Summary of the Invention [Problem to be solved by the invention]

[0004] The correction fluid and white ink disclosed in Patent Document 1 and Patent Document 2 are thought to work to improve the redispersibility of titanium oxide. However, it was found that users of commercially available products did not have much of an impression that the redispersibility was good, and as a result of detailed research by the present inventors, new problems caused by the way the correction fluid is used were revealed. That is, the normal method of using correction fluid is to move an agitator such as a metal rod contained in a container together with the correction fluid by shaking the container, etc., to agitate the correction fluid in the container before applying it, but this agitation followed by application and then leaving it to stand for a certain period of time is repeated, and since it is only used when making typos, the unused state often lasts for a certain period of time, and when this agitation, application, and then leaving it to stand for a certain period of time is repeated, gradually shaking the container several times when using it does not form a sufficient dispersion state of titanium oxide, and only a thin liquid is discharged or a viscous substance is discharged, and a uniform coating film is not formed, resulting in insufficient hiding power for typos, etc. This is thought to be due to the phenomenon that the sedimentation layer gradually becomes a hard cake due to the accumulation of insufficient agitation or insufficient agitation with each use, and conventional correction fluids including those in Patent Documents 1 and 2 have only evaluated redispersibility over a long period of time after one use, and have not paid attention to problems with repeated use.

[0005] The object of the present invention is to provide a correction fluid that can form a good coating film even after repeated stirring, application and leaving to stand for a long period of time. [Means for solving the problem]

[0006] The present invention relates to a method for producing a titanium dioxide particle having a major axis of 1.6 μm or more and a minor axis of 0.1 μm or more and a minor axis of 1.3 μm or less, and an aspect ratio (major axis / minor axis) of 5 or more. and has hydroxyl groups on the surface. The present invention relates to a correction fluid that contains at least one or a mixture of two or more particles selected from the group consisting of dry silica, fatty acid amide, modified urea, polyethylene oxide, and bentonite. The particles have a major axis of 1.6 μm or more and a minor axis of 0.1 μm or more and a minor axis of 1.3 μm or less, an aspect ratio (major axis / minor axis) of 5 or more, and have hydroxyl groups on the surface thereof, and are one or a mixture of two or more particles selected from calcium carbonate, titanium oxide, and silicon nitride.The second gist is as follows: The particle has a major axis of 1.6 μm or more and a minor axis of 0.1 μm or more and a minor axis of 1.3 μm or less, an aspect ratio (major axis / minor axis) of 5 or more, and a weight ratio of the particle having a hydroxyl group on the surface to one or a mixture of two or more selected from dry silica, fatty acid amide, modified urea, polyethylene oxide, and bentonite is 5 or more and 1500 or less. The third point is: The fourth gist is that the particles are calcium carbonate having a major axis of 1.6 μm or more and 170 μm or less, a minor axis of 0.1 μm or more and 1.3 μm or less, and an aspect ratio (major axis / minor axis) of 5 or more, and the difference in specific gravity from dry silica is 0.7 or less. Effect of the Invention

[0007] Dry silica, fatty acid amides, modified urea, polyethylene oxide, and bentonite are known to be substances that form loose aggregates in hydrocarbon solvents in which the chains are connected like branched chains and which undergo repeated partial aggregation and dispersion in response to external forces. However, due to the presence of particles within such loose aggregates with major axes between 1.6 μm and 170 μm, minor axes between 0.1 μm and 1.3 μm, and aspect ratios (major axis / minor axis) of 5 or more, it is presumed that the structure of the aggregates made of dry silica, fatty acid amides, modified urea, polyethylene oxide, and bentonite is not uniform, and an overall structure that varies in density and roughness is formed. Particles with a major axis of 1.6 μm or more and 170 μm or less, a minor axis of 0.1 μm or more and 1.3 μm or less, and an aspect ratio (major axis / minor axis) of 5 or more have a shape that is significantly different from other particles, and are sufficiently coarse compared to the above-mentioned substances such as dry silica, which inhibits the formation of a hard aggregate structure that would become dense, and also exhibits a stirring effect that greatly affects the aggregated state due to the influence of external forces, resulting in a composite aggregate structure that is easy to flow.It is presumed that this inhibits the formation of a hard caking structure in which titanium oxide densely aggregates, and while the composite aggregate structure predominantly maintains the dispersed state of titanium oxide over the long term, it forms loose aggregates that are easy to stir, and even if the mixture is repeatedly stirred, applied, and then left to stand again, it is not subjected to the pressing action of the stirrer and prevents hard caking, and neither a thin liquid nor a viscous substance is ejected, and a uniform coating film is formed that reliably conceals typographical errors. Furthermore, by making the particles have a major axis of 1.6 μm or more and 170 μm or less, a minor axis of 0.1 μm or more and 1.3 μm or less, and an aspect ratio (major axis / minor axis) of 5 or more and have hydroxyl groups on the surface, it is presumed that the particles form hydrogen bonds with the dry silica, fatty acid amide, modified urea, polyethylene oxide, and bentonite, thereby further suppressing the formation of a hard cake by titanium oxide. Furthermore, the particles having a major axis of 1.6 μm or more and 170 μm or less, a minor axis of 0.1 μm or more and 1.3 μm or less, and an aspect ratio (major axis / minor axis) of 5 or more are a mixture of one or more materials selected from calcium carbonate, titanium oxide, and silicon nitride, which are more rigid than organic substances, thereby making it possible to efficiently exert the stirring effect on the complex, loosely aggregated structure with the dry silica, fatty acid amide, modified urea, polyethylene oxide, and bentonite. Furthermore, by having a weight ratio in the correction fluid of particles having a major axis of 1.6 μm or more and 170 μm or less, a minor axis of 0.1 μm or more and 1.3 μm or less, and an aspect ratio (major axis / minor axis) of 5 or more, and a mixture of one or more selected from dry silica, fatty acid amide, modified urea, polyethylene oxide, and bentonite of 5 or more and 1500 or less, the titanium oxide is maintained in a dispersed state while being efficiently present in the aggregates of dry silica, fatty acid amide, modified urea, polyethylene oxide, and bentonite, forming a composite aggregate structure that is gentler and easier to stir, and also making the stirring effect more efficient, which is more preferable. Furthermore, the particles are calcium carbonate having a major axis of 1.6 μm or more and 170 μm or less, a minor axis of 0.1 μm or more and 1.3 μm or less, and an aspect ratio (major axis / minor axis) of 5 or more, and the difference in specific gravity from the dry silica is 0.7 or less, so that separation due to a difference in settling velocity from the composite aggregated structure is unlikely to occur, the particles and the dry silica are prevented from being separated, the composite aggregated structure is easily maintained, and the effects due to the above-mentioned gentle aggregation and the stirring effect are easily exhibited efficiently. [Brief description of the drawings]

[0008] [Figure 1] Overall longitudinal cross-sectional view of the applicator [Diagram 2] Enlarged view of part I in Fig. 1 [Diagram 3] FIG. 1 is a perspective view showing a state in which the applicator is used DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The titanium oxide used in the correction fluid of the present invention is a white pigment with high hiding power, and those whose surfaces have been treated with alumina or silica can also be used. Specific examples of titanium oxide include TITONE SR-1, TITONE R-650, TITONE R-62N, TITONE R-42, TITONE R-7E, TITONE R-21, TITONE R-25, TITONE R-32, TITONE R-5N, TITONE R-45M, and TITONE TCR-10 (all manufactured by Sakai Chemical Industry Co., Ltd.), Kronos KR-310, KR-380, and Kronos 480 (all manufactured by Titanium Industry Co., Ltd.), Typure R-900, TITONE R-902, TITONE R-960, and TITANIX (all manufactured by DuPont Japan Limited). Examples of titanium oxide include JR-301, JR-805, JR-806, JR-603, JR-800, JR-403, JR-701, JRNC, and JR-605 (all manufactured by Teika Co., Ltd.), TIPAQUE R-820, R-830, R-550, R-780, and R-780-2 (all manufactured by Ishihara Sangyo Kaisha, Ltd.). These titanium oxides may be used alone or in combination of two or more. The amount of titanium oxide added is preferably 20% by weight or more and 60% by weight or less based on the total amount of correction fluid in terms of hiding power.

[0010] Hydrocarbon solvents are used to adjust the viscosity of the correction fluid, specifically, normal pentane (boiling point 36.0°C), cyclopentane (boiling point 49.2°C), methylcyclopentane (boiling point 71.8°C), normal hexane (boiling point 68.7°C), 2-methylpentane (boiling point 60.2°C), 3-methylpentane (boiling point 63.2°C), 2,2-dimethylbutane (boiling point 49.7°C), 2,3-dimethylbutane (boiling point 58.0°C), normal heptane (boiling point 98.4°C), 2-methyl Dimethylhexane (boiling point 90.0°C), 3-methylhexane (boiling point 91.8°C), 2,2-dimethylhexane (boiling point 79.2°C), 2,3-dimethylpentane (boiling point 89.7°C), 2,4-dimethylpentane (boiling point 80.5°C), 3,3-dimethylpentane (boiling point 86.0°C), 3-ethylpentane (boiling point 93.4°C), 2,2,3-trimethylbutane (boiling point 80.0°C), normal octane (boiling point 125.6°C), 4-methylheptane (boiling point 117.7°C), 2-methylheptane (boiling point 117.7°C), 117.6°C), 3-methylheptane (boiling point 118.9°C), 2,2-dimethylhexane (boiling point 108.8°C), 2,3-dimethylhexane (boiling point 115.6°C), 2,4-dimethylhexane (boiling point 109.4°C), 2,5-dimethylhexane (boiling point 109.1°C), 3,3-dimethylhexane (boiling point 111.9°C), 3,4-dimethylhexane (boiling point 117.7°C), 3-ethylhexane (boiling point 118.5°C), 2,2,3-trimethylpentane (boiling point 10 9.8°C), 2,2,4-trimethylpentane (boiling point 99.2°C), 2,3,3-trimethylpentane (boiling point 114.7°C), 2,3,4-trimethylpentane (boiling point 113.4°C), 2-methyl-3-ethylpentane (boiling point 115.6°C), 3-methyl-3-ethylpentane (boiling point 118.2°C), cyclohexane (boiling point 80.0°C), methylcyclohexane (boiling point 100.9°C), ethylcyclohexane (boiling point 132°C), and other aliphatic hydrocarbon solvents. Commercially available examples include Marukasol FH (cyclopentane, manufactured by Maruzen Petrochemical Co., Ltd.), methylcyclohexane (manufactured by Sankyo Chemical Co., Ltd.), and Exxol DSP 100 / 140 (cyclic aliphatic hydrocarbon solvent, initial boiling point 102°C, dry point 138°C) (manufactured by ExxonMobil (USA)).2-Methylpentane, 3-methylpentane, 2,2-dimethylbutane, and 2,3-dimethylbutane are collectively called isohexane, and a commercially available example thereof is high-purity isohexane (manufactured by Sankyo Chemical Co., Ltd.). 2-Methylhexane, 3-methylhexane, 2,2-dimethylhexane, 2,3-dimethylpentane, 2,4-dimethylpentane, 3,3-dimethylpentane, 3-ethylpentane, and 2,2,3-trimethylbutane are collectively called isoheptane, and a commercially available example thereof is isoheptane (manufactured by Tokyo Chemical Industry Co., Ltd.). 4-Methylheptane, 2-methylheptane, 3-methylheptane, 2,2-dimethylhexane, 2,3-dimethylhexane, 2,4-dimethylhexane, 2,5-dimethylhexane, 3,3-dimethylhexane, 3,4-dimethylhexane, 3-ethylhexane, 2,2,3-trimethylpentane, 2,2,4-trimethylpentane, 2,3,3-trimethylpentane, 2,3,4-trimethylpentane, 2-methyl-3-ethylpentane, and 3-methyl-3-ethylpentane are collectively called isooctane, and examples of commercially available solvents include Marukasol 8 (manufactured by Maruzen Petrochemical Co., Ltd.) and isooctane (manufactured by Sankyo Chemical Co., Ltd.). Considering the drying property of the coating film, it is preferable that these hydrocarbon solvents have a boiling point of 40 to 150°C. These hydrocarbon solvents can be used alone or in combination, and it is preferable that the amount of the solvent used is 30 to 60% by weight based on the total amount of correction fluid, since good coating properties can be obtained.

[0011] Particles having a major axis of 1.6 μm or more and 170 μm or less, a minor axis of 0.1 μm or more and 1.3 μm or less, and an aspect ratio (major axis / minor axis) of 5 or more can be used in combination with one or a mixture of two or more selected from dry silica, fatty acid amide, modified urea, polyethylene oxide, and bentonite to provide a correction fluid that can form a good coating film even after repeated stirring, application, and leaving to stand for long periods of time. Examples of particles having a major axis of 1.6 μm or more and 170 μm or less, a minor axis of 0.1 μm or more and 1.3 μm or less, and an aspect ratio (major axis / minor axis) of 5 or more include silicon nitride whiskers, silicon carbide whiskers, aluminum borate whiskers, zinc oxide whiskers, potassium titanate whiskers, whisker-like calcium carbonate, whisker-like titanium oxide, alumina whiskers, magnesia whiskers, mullite whiskers, magnesium borate whiskers, titanium boride whiskers, alumina and alumina-silica short fibers, silica short fibers, zirconia fibers (short fibers), and kaolin-based ceramic short fibers. Specific examples of commercially available products include FTL-100 (major axis 1.68 μm, minor axis 0.13 μm, aspect ratio 12.9, specific gravity 4.2, titanium oxide having hydroxyl groups on the surface), FTL-200 (major axis 2.86 μm, minor axis 0.21 μm, aspect ratio 13.6, specific gravity 4.2, titanium oxide having hydroxyl groups on the surface), and FTL-300 (major axis 5.15 μm, minor axis 0.27 μm, aspect ratio 19. Examples of the whiskers include: titanium oxide (long diameter 20 μm, short diameter 1 μm, aspect ratio 20.0, specific gravity 2.86, calcium carbonate with hydroxyl groups on the surface, manufactured by Maruo Calcium Co., Ltd.), Silar (long diameter 40 μm, short diameter 0.55 μm, aspect ratio 72.7, specific gravity 3.2, silicon carbide with hydroxyl groups on the surface, manufactured by Haydale Technologies Inc (UK)), silicon nitride whiskers (long diameter 170 μm, short diameter 1.3 μm, aspect ratio 130.7, specific gravity 3.18, silicon nitride with hydroxyl groups on the surface, manufactured by Tateho Chemical Industries Co., Ltd.). The long diameter and aspect ratio of the particles can also be adjusted by crushing the above particles using a planetary ball mill or the like.If the amount of particles with a major axis of 1.6 μm or more and 170 μm or less, a minor axis of 0.1 μm or more and 1.3 μm or less, and an aspect ratio (major axis / minor axis) of 5 or more is 5% by weight or more and 15% by weight or less relative to the total amount of correction fluid, they will be present in an amount that can exert a stirring effect in the correction fluid, and it is thought that they will easily form a composite aggregate structure that is easy to flow within the aggregates of dry silica, fatty acid amide, modified urea, polyethylene oxide, and bentonite, and even if stirring, application, and leaving it to stand for a long period of time are repeated, the formation of a good coating film will be maintained, and stable ejection of correction fluid will also be obtained, which is preferable. Particles having a major axis of 1.6 μm or more and 170 μm or less, a minor axis of 0.1 μm or more and 1.3 μm or less, and an aspect ratio (major axis / minor axis) of 5 or more are preferably those having a major axis of 1.6 μm or more and 170 μm or less, a minor axis of 0.1 μm or more and 1.3 μm or less, and an aspect ratio (major axis / minor axis) of 5 or more and 131 or less, because these particles have good fluidity, are rigid and less likely to break, and can maintain a good stirring effect. Furthermore, it is particularly preferable that the major axis is 5 μm or more and 40 μm or less, the minor axis is 0.2 μm or more and 1 μm or less, and an aspect ratio (major axis / minor axis) of 8 or more and 73 or less, because these particles have even better fluidity, are less likely to break, and can further maintain a good stirring effect. Particles having a major axis of 1.6 μm or more and 170 μm or less, a minor axis of 0.1 μm or more and 1.3 μm or less, and an aspect ratio (major axis / minor axis) of 5 or more will have a sufficiently coarse particle diameter relationship when the average particle diameter of the primary particles of the mixture of one or more types selected from dry silica, fatty acid amide, modified urea, polyethylene oxide, and bentonite that form aggregates around them is 7 nm or more and 30 nm or less, and the stirring effect will efficiently exert the effect of greatly affecting the aggregated state due to the influence of external forces.

[0012] When particles having a major axis of 1.6 μm or more and 170 μm or less, a minor axis of 0.1 μm or more and 1.3 μm or less, and an aspect ratio (major axis / minor axis) of 5 or more have hydroxyl groups on the surface, it is presumed that the particles form hydrogen bonds with dry silica, fatty acid amide, modified urea, polyethylene oxide, and bentonite, and a composite structure with some roughness and density as a whole consisting of the particles having a major axis of 1.6 μm or more and 170 μm or less, a minor axis of 0.1 μm or more and 1.3 μm or less, and an aspect ratio (major axis / minor axis) of 5 or more and the aggregates of dry silica, fatty acid amide, modified urea, polyethylene oxide, and bentonite is likely to be maintained, and a loose, easily stirred aggregated state is maintained, and when the particles are repeatedly stirred, applied, and left to stand again, a uniform coating film is formed without ejecting only a thin liquid or a viscous substance, and without ejecting a viscous substance, which reliably conceals typographical errors.

[0013] Dry silica is produced by combustion hydrolysis of silicon tetrachloride in a gas phase (dry method), and has a structure and properties different from wet silica such as white carbon and silica gel produced by the reaction of sodium silicate with acid (wet method). Dry silica is a primary particle and does not have an internal surface area, so it has a low bulk density (bulk specific gravity: 30-60g / L) and a small primary particle size (average primary particle size: 7-40nm). In addition, wet silica has a very large internal surface area, a relatively high bulk specific gravity (130-400g / L), and a large primary particle size (average primary particle size: 150-7000nm). Furthermore, dry silica forms loose aggregates in a hydrocarbon solvent that are connected like a branched chain due to hydrogen bridge bonds between silanol groups on the particle surface, and partially repeats aggregation and dispersion in response to external forces. Specific examples of dry silica include Aerosil 130 (average particle size of primary particles: 16 nm, bulk density: 50 g / L, specific gravity: 2.2), Aerosil 200 (average particle size of primary particles: 12 nm, bulk density: 50 g / L, specific gravity: 2.2), Aerosil 300 (particle size: 7 nm, bulk density: 50 g / L, specific gravity: 2.2), Aerosil 380 (average particle size of primary particles: 7 nm, bulk density: 50 g / L, specific gravity: 2.2), Aerosil R972 (hydrophobic dry silica whose surface is covered with methyl groups and hydrophobized, average particle size of primary particles: 16 nm, bulk density: 50 g / L, specific gravity: 2.2), Aerosil 50 (average particle size of primary particles: 30 nm, bulk density: 50 g / L, specific gravity: 2.2), Aerosil 400 (average particle size of primary particles: 40 nm, bulk density: 50 g / L, specific gravity: 2.2), Aerosil 50 (average particle size of primary particles: 3 ...400 (particle size: 7 nm, bulk density: 50 g / L, specific gravity: 2.2), Aerosil 50 (particle size: 30 nm, bulk density: 50 g / L, specific gravity: 2.2), Aerosil 400 (particle size: 30 nm, bulk density: 50 g / L, specific gravity: 2.2), Aerosil 400 (particle size: 30 nm, bulk density: 50 g / L, specific gravity: 2.2), Aerosil 40 2.2), RX200 (hydrophobic dry silica whose surface is covered with methyl groups and hydrophobized, average particle size of primary particles is 12 nm, bulk density is 50 g / L, specific gravity is 2.2), R976-S (hydrophobic dry silica whose surface is covered with methyl groups and hydrophobized, average particle size of primary particles is 7 nm, bulk density is 50 g / L, specific gravity is 2.2), R972CF (hydrophobic dry silica whose surface is covered with methyl groups and hydrophobized, particle size is 16 nm, bulk density is 30 g / L, specific gravity is 2.2), TT600 (particle size is 40 nm, bulk density is 60 g / L, specific gravity is 2.2) (all manufactured by Nippon Aerosil Co., Ltd.). The amount of dry silica used can be 0.01 to 1% by weight based on the total amount of correction fluid in order to form a thin coating film with good ejection properties and drying properties. Hydrophobic dry silica, the surface of which is hydrophobized by covering with methyl groups, is preferred because it is easily wetted by hydrocarbon solvents and can form stable aggregated particles.

[0014] The fatty acid amide is an organic amide wax made of fatty acid and amine, and specific examples thereof include A670-20M, A671-EZ, 6820-20M, 6820-10M, and FS-6010 (all manufactured by Kusumoto Chemicals Co., Ltd.). When the amount of fatty acid amide used is 0.01 to 1.5% by weight based on the total amount of correction fluid, it is easy to discharge, a thin coating film can be formed, the coating film dries easily, and a good correction fluid can be obtained.

[0015] Modified urea is a substance consisting of a structure in which urea groups and low polar groups are linked in a long chain, and specific examples include BYK-410, BYK-411, and BYK7411ES (all manufactured by BYK-Chemie (Germany)). When the amount of modified urea used is 0.01 to 1% by weight based on the total amount of correction fluid, it is easy to eject, a thin coating can be formed, the coating is easy to dry, and a good correction fluid can be obtained.

[0016] Oxidized polyethylene is a wax in which polyethylene is oxidized to introduce polar groups, and specific examples include PF-920, PF-911, PF-930, and 4401-25M (all manufactured by Kusumoto Chemicals Co., Ltd.). When the amount of oxidized polyethylene used is 0.01 to 1% by weight based on the total amount of correction fluid, it is easy to eject, a thin coating can be formed, the coating is easy to dry, and a good correction fluid can be obtained.

[0017] The bentonite is preferably organic bentonite modified with quaternary ammonium cations or the like, since it is easily wetted by hydrocarbon solvents and can form stable aggregated particles. Specific examples of organic bentonite include Esben N-400, Esben W, Esben NX, Esben NX80, Esben NZ, Esben NZ70 (all manufactured by Hojun Co., Ltd.), CLAYTONE-AF, CLAYTONE-APA, and CLAYTONE-HY (all manufactured by BYK-Chemie, Germany). When the amount of bentonite used is 0.01 to 1% by weight based on the total amount of correction fluid, it is easy to discharge, a thin coating film can be formed, the coating film dries easily, and a good correction fluid can be obtained.

[0018] When the weight ratio in the correction fluid of particles having a major axis of 1.6 μm or more and a minor axis of 0.1 μm or more and a minor axis of 0.1 μm or more and a minor axis of 1.3 μm or less and an aspect ratio (major axis / minor axis) of 5 or more and a mixture of one or more selected from dry silica, fatty acid amide, modified urea, polyethylene oxide, and bentonite is 5 or more and 1500 or less, the titanium oxide is maintained in a dispersed state while being efficiently present in the aggregates of dry silica, fatty acid amide, modified urea, polyethylene oxide, and bentonite, forming a composite aggregate structure that is gentler and easier to stir, and also making the stirring effect more efficient, it is preferable. The above weight ratio is calculated by dividing the weight of particles in the correction fluid having a major axis of 1.6 μm or more and 170 μm or less, a minor axis of 0.1 μm or more and 1.3 μm or less, and an aspect ratio (major axis / minor axis) of 5 or more, by the weight of one or a mixture of two or more selected from dry silica, fatty acid amide, modified urea, polyethylene oxide, and bentonite, in the correction fluid.

[0019] By having the ratio of the volume occupancy in the correction fluid between the particles having a major axis of 1.6 μm or more and 170 μm or less, a minor axis of 0.1 μm or more and 1.3 μm or less, and an aspect ratio (major axis / minor axis) of 5 or more and the dry silica be 3.8 or more and 1153.8 or less, the silanol groups on the surface of the dry silica form hydrogen bonds with the particles having a major axis of 1.6 μm or more and 170 μm or less, a minor axis of 0.1 μm or more and 1.3 μm or less, and an aspect ratio (major axis / minor axis) of 5 or more, and a composite structure can be formed with high reproducibility, and while maintaining the titanium oxide in a dispersed state, the aggregates are gentler and easier to stir, and the stirring effect can be made highly efficient, which is preferable. The volume occupancy ratio in the present invention is calculated by the following formula 1. Formula 1: Ratio of volume occupancy of compound A and compound B = (mass of compound A in correction fluid / specific gravity of compound A) / (mass of compound B in correction fluid / specific gravity of compound B)

[0020] When the particles are calcium carbonate and have a major axis of 1.6 μm or more and 170 μm or less, a minor axis of 0.1 μm or more and 1.3 μm or less, and an aspect ratio (major axis / minor axis) of 5 or more, and the difference in specific gravity with dry silica is 0.7 or less, it is presumed that this will maintain a gentle, easily agitated aggregated state, prevent the particles and dry silica from being separated from the composite structure, and allow the effects of the gentle agglomeration and the agitation to be efficiently exhibited, which is preferable because it allows the effects of the gentle agglomeration and the agitation to be efficiently exhibited.

[0021] In addition to these essential ingredients, other materials may be included for various purposes. Resins soluble in hydrocarbon solvents can be used to disperse pigments and fix correction fluid to paper surfaces. Examples of resins soluble in hydrocarbon solvents that can be used include maleic acid resins, alkyd resins, thermoplastic elastomers, petroleum resins, terpene resins, terpene phenol resins, and rosin-based resins. Considering pigment dispersibility and fixability to paper surfaces, acrylic resins are preferred. Copolymers of various monomers can be used as acrylic resins. Usable monomers include acrylic esters such as methyl acrylate, ethyl acrylate, isopropyl acrylate, normal butyl acrylate, and 2-ethylhexyl acrylate; methacrylic esters such as methyl methacrylate, ethyl methacrylate, propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, 2-ethylhexyl methacrylate, octyl methacrylate, lauryl methacrylate, cetyl methacrylate, stearyl methacrylate, oleyl methacrylate, cyclohexyl methacrylate, and benzyl methacrylate; and monomers containing amino groups such as N,N-dimethylaminopropyl (meth)acrylate, N,N-diethylaminopropyl (meth)acrylate, and N,N-dibutylaminoethyl (meth)acrylate. acrylate, N,N-dipropylaminoethyl (meth)acrylate, N,N-diisopropylaminoethyl (meth)acrylate, N,N-di-tert-butylaminoethyl (meth)acrylate, N,N-dicyclohexylaminoethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylamide, N,N-diethylaminoethyl (meth)acrylamide N,N-dimethylaminopropyl (meth)acrylamide, N,N-diethylaminopropyl (meth)acrylamide, vinyl monomers include vinyl acetate, styrene, vinyl toluene, maleic acid, itaconic acid, 2-hydroxyethyl methacrylate, hydroxypropyl methacrylate, 2-hydroxypropyl acrylate, hydroxypropyl acrylate, acrylamide, N-tyrol acrylamide, diacetone acrylamide, and glycidyl methacrylate.The amount of resin soluble in a hydrocarbon solvent used is preferably such that the resin solid content is 3 to 15% by weight of the total correction fluid, since this provides sufficient fixability to enable rewriting.

[0022] Furthermore, white, black or chromatic pigments can be used in combination to match the color tone of the correction fluid, and extender pigments and resin particles can be used to improve hiding power. Specific examples include spherical and agglomerated particles such as carbon fine titanium oxide, crosslinked polymethyl methacrylate, benzoguanamine-formaldehyde condensate, benzoguanamine-melamine-formaldehyde condensate, melamine-formaldehyde condensate, wet silica, aluminum silicate, and calcium carbonate, and plate-shaped particles such as mica, talc, boron nitride, and molybdenum disulfide. Examples of aluminum silicate include Kyoward 700 (aluminum silicate, manufactured by Kyowa Chemical Industry Co., Ltd.). As coloring pigments, yellow iron oxide and low-order titanium oxide are preferable because they have a smaller specific gravity difference than titanium oxide, so there is less difference in sedimentation rate and the color tone is less likely to change. Yellow iron oxide is a yellow pigment, and preferred examples of commercially available yellow iron oxide include Tarox LL-XLO, Tarox LL-100, Tarox LEMON, Tarox HY-100, Tarox HY-200, and Tarox HY-250 (all manufactured by Titanium Kogyo Co., Ltd.), Bayferrox 415, Bayferrox 420, Bayferrox 1420, Bayferrox 3420, Bayferrox 1420M, Bayferrox 910, Bayferrox 920, Bayferrox 930, Bayferrox 940, Bayferrox 943, Bayferrox 960, Bayer 3905, Bayferrox 3910, Bayferrox 3920, Bayferrox 3950, Bayferrox 920Z, and Bayferrox 1920 (all manufactured by Bayer Co., Ltd.), YP-200N, YP-100N, and YP-50N (all manufactured by Tone Sangyo Co., Ltd.). These yellow iron oxides can be used alone or in combination of two or more, and the amount used is preferably 0.01 to 5% by weight based on the total amount of correction fluid. Low-order titanium oxide is a black pigment, and commercially available low-order titanium oxides include black conductive titanium oxide M-1 and S-1 (both manufactured by Ishihara Sangyo Kaisha Ltd.) and Tilack D (manufactured by Ako Kasei Co., Ltd.). These low-order titanium oxides can be used alone or in combination of two or more, and the amount used is preferably 0.01 to 5% by weight based on the total amount of correction fluid.Other pigments that can be used include PV FAST YELLOW H2G (CI Pigment Yellow), PV FAST YELLOW H3R-LHC (CI Pigment Yellow 181), PV FAST BLUE BG (CI Pigment Blue 15:3) (all manufactured by Clariant Chemicals K.K.), T-18N Signal Green (green fluorescent pigment, DayGlo Inc. (USA)), and Chromofine Red 6820 (CI Pigment Violet 19, manufactured by Dainichiseika Color & Chemicals Mfg. Co., Ltd.).

[0023] To improve the dispersion stability of titanium oxide, pigments, etc., dispersants such as anionic surfactants such as alkyl sulfate ester salts, alkyl phosphates, and polycarboxylic acid polymers; nonionic surfactants such as polyethylene alkyl ethers, glycerin fatty acid esters, and polyoxyethylene fatty acid esters; quaternary ammonium salts; and alkylamine salts can be added.

[0024] The correction fluid of the present invention can be obtained by dispersing and mixing the above-mentioned components using an agitating disperser such as a ball mill, an attritor, a sand grinder, or an impeller.

[0025] An example of an applicator that preferably uses the correction fluid of the present invention will be described with reference to the attached drawings. However, the dimensions, materials, shapes, relative positions, etc. are not limited to this, and the correction fluid of the present invention can also be filled and used in other applicator structures, such as a brush-type fountain pen applicator, a ballpoint pen tip applicator, or a pressurized type applicator in which compressed air is already built into the correction fluid tank.

[0026] As shown in FIG. 1 and FIG. 2, which is an enlarged view of part I in FIG. 1, the pen is composed of a cylindrical rear barrel 2 with a bottom, which is a blow-molded product made of flexible polyamide resin that can contain correction fluid 1, a cut stainless steel tip 3 for opening an outlet 3a to discharge correction fluid 1 to the outside, a front barrel 4 which is an injection-molded product made of polybutylene terephthalate resin that connects the rear barrel 2 and the tip 3, and an applicator 6 which is an injection-molded product made of polyacetal resin with excellent self-lubricating properties. As shown in FIG. 3, which is a perspective view showing the applicator in use, the application body 6 can more effectively form a smooth coating 5 of the discharged correction fluid.

[0027] The rear barrel 2 is flexible enough to be deformed, and when the correction fluid 1 is discharged, the inside of the rear barrel 2 is compressed and pressurized by the pressure deformation such as by gripping it tightly with the hand that holds it, and the correction fluid 1 is supplied to the opened discharge port 3a. Of course, the means for compressing and pressurizing the inside of the rear barrel 2 is not limited to that in this example, and can be appropriately set according to the specifications of the applicator, such as a pump pressurizing mechanism that pressurizes the inside of the rear barrel 2 by knocking the rear end. Furthermore, the material is not limited to polyamide resin as in this example, and may be polyacetal resin, polybutylene terephthalate resin, polybutylene naphthalate resin, fluororesin, etc., as long as it does not react with the correction fluid 1 and has flexibility enough to be deformed. In addition, the inside of the rear barrel 2 contains an agitator 7 made of carbon steel that can agitate the correction fluid 1 by shaking the container, etc. In this example, one rod-shaped carbon steel is placed in the stirrer 7, but the material, shape, and number of stirrers 7 are appropriately set according to the ingredients of the correction fluid 1 and the size and shape of the rear axle 2. In particular, if the stirrer has a relatively high specific gravity and is non-reactive with the correction fluid 1 contained inside the rear axle 2, the correction fluid can be stirred efficiently.

[0028] The front barrel 4 has a through hole, and is arranged to communicate with the rear barrel 2 and the tip 3 so that the correction fluid 1 contained in the rear barrel 2 can be discharged from the discharge port 3a of the tip 3, so as to relay the rear barrel 2 and the tip 3. In this example, the front barrel 4 and the rear barrel 2 are joined by a detachable screw thread, making it possible to fill the correction fluid 1 during manufacturing and to replenish the correction fluid 1 after use, but as long as the front barrel 4 has a through hole, depending on the means of filling the correction fluid 1 during manufacturing, the joining means of the rear barrel 2 and the tip 3 is not limited to screwing or press-fitting, and as long as it is possible to suppress the evaporation or outflow of the solvent of the correction fluid 1 from the joint by sealing, the rear barrel 2 may be joined by press-fitting, or the rear barrel 2 and / or the tip 3 may be bonded by melting or with an adhesive. The material of the front barrel 4 is not limited to the injection molded product made of polybutylene terephthalate resin as in this example, but may be any material that does not react with the correction fluid 1 and can relay the rear barrel 2 and the tip 3, and may be made of, for example, synthetic resins such as polyamide resin, polyacetal resin, polybutylene naphthalate resin, and fluororesin, as well as metal and glass. In addition, although not shown, a cap is arranged on the front barrel 4 to cover the tip 3 and the applicator 6 and block the outside air, in order to suppress the obstruction of the opening of the outlet 3a of the tip 3 when in use due to the drying of the correction fluid 1 when not in use. Furthermore, since the front barrel 4 has a through hole and serves as a relay between the rear barrel 1 and the tip 3, it is not necessary to arrange the front barrel 4 as long as the rear barrel 1, the tip 3, and the applicator 6 can be joined, and the above-mentioned cap is arranged detachably to cover the tip 3 and the applicator 6 and block the outside air. It is not necessary to use a cap, and the dried correction fluid 1 that is produced when the tip is not used may be destroyed when the tip is used to open the discharge port 3a of the tip 3 and enable the correction fluid 1 to be discharged.

[0029] The inside of the tip 3 is a so-called valve mechanism in which, when not in use, the core body 9 is biased against the blocking part 3b and presses against the blocking part 3b to block the discharge port 3a by the installation of a coil spring 8 as an elastic member having a strength that prevents the correction fluid 1 from leaking out from the discharge port 3a, and the core body 9 retracts to release the pressure contact with the blocking part 3b. The tip 9a of the core body 9 is configured to protrude further toward the surface to be coated than the tip 6b of the protruding part 6a of the applicator 6 in order to contact the surface to be coated with the core body 9 and retract when in use, releasing the pressure contact by the coil spring 8 as an elastic member to open the discharge port 3a. The size of the discharge port 3a that opens when the core body 9 contacts the surface to be contacted and is pressed is set to a preferable amount so that the coating film 5 can be formed more effectively and smoothly when the correction fluid 1 is discharged, but is appropriately set according to the shape and size of the applicator 6 and the specifications of the discharge amount. In this example, a stainless steel coil spring 8 and a machined stainless steel tip 3 and core 9 are used, but as long as there is no problem with reactivity with the correction fluid 1, sealing properties, or opening and closing of the discharge port 3a, the materials and machined processes are not limited to those of this example, and each or some of these parts may be made from injection molded products made of polyacetal resin, polybutylene terephthalate resin, polyamide resin, polybutylene naphthalate resin, fluororesin, etc.

[0030] The applicator 6 has two protrusions 6a arranged at positions facing each other and parallel to each other from the base 6c, which is approximately on the same line in the radial direction as the discharge port 3a of the tip 3. As a result, when the core 9 contacts the contact surface during use and the discharge port 3a opens, the correction fluid 1 spreads to the area surrounded by the protrusions 6a and base 6c of the applicator 6 and the contact surface. As shown in the perspective view of the applicator in use in Figure 3, by applying the correction fluid 1 while it is spread to the area surrounded by the protrusions 6a and base 6c of the applicator 6 and the contact surface, a very uniform coating 5 of the correction fluid 1 is formed, and the coating 5 of the correction fluid 1 can be formed more effectively and smoothly. In addition, the applicator 6 in this example is formed from an injection molded product made of polyacetal resin with excellent self-lubricating properties, and the portion of the protrusion 6a that contacts the contact surface is curved to suppress catching and frictional resistance with the contact surface, making it easier to apply smoothly, but as long as it does not react with the correction fluid 1, the material may be synthetic resin such as polybutylene terephthalate resin, polyamide resin, polybutylene naphthalate resin, fluororesin, metal, glass, etc. Furthermore, the protrusion 6a may be attached as a part separate from the applicator 6, and the shape of the protrusion 6a is not limited to a curved shape, and the material and shape can be appropriately set according to the specifications of the applicator. EXAMPLES

[0031] The present invention will now be described in detail with reference to examples.

[0032] (Making correction fluid) The following Tables 1 to 10 show the correction fluids of Examples 1 to 41 and Comparative Examples 1 to 10, as well as the results of various tests described below. For the correction fluids of the Examples and Comparative Examples, each component except for particles 1 to 14 was dispersed in a planetary ball mill (Planetary Ball Mill Quartet P-5, Fritsch, Germany) with φ2 mm beads at 250 rpm for 30 minutes, and particles 1 to 14 corresponding to the table were added and stirred for 1 hour with a three-one motor to obtain the correction fluid. Specifically, the following compounds were used.

[0033] <Titanium oxide> Titanium oxide-1: TITONE R-7E (titanium oxide, manufactured by Sakai Chemical Industry Co., Ltd.) Titanium oxide-2: TITONE R-62N (titanium oxide, manufactured by Sakai Chemical Industry Co., Ltd.) Titanium oxide-3: TITANIX JR-800 (titanium oxide, manufactured by Teika Co., Ltd.) Titanium oxide-4: TITANIX JR-805 (titanium oxide, manufactured by Teika Co., Ltd.) Titanium dioxide-5: TIPAQUE R-780 (titanium dioxide, manufactured by Ishihara Sangyo Kaisha, Ltd.) Titanium oxide-6: TIPAQUE R-780-2 (titanium oxide, manufactured by Ishihara Sangyo Kaisha, Ltd.) Titanium oxide-7: TITONE R-5N (titanium oxide, manufactured by Sakai Chemical Industry Co., Ltd.) Titanium dioxide-8: Chronos KR-380 (titanium dioxide, manufactured by Titanium Kogyo Co., Ltd.)

[0034] <Resin soluble in hydrocarbon solvents> Resin-1: Dianale BR-105 (acrylic resin, manufactured by Mitsubishi Chemical Corporation) Resin-2: Dianale BR-115 (acrylic resin, manufactured by Mitsubishi Chemical Corporation) Resin-3: Dianale BR-1122 (acrylic resin, manufactured by Mitsubishi Chemical Corporation) Resin-4: Acryloid B-67 (acrylic resin, manufactured by Rohm & Haas (USA))

[0035] <Hydrocarbon solvent> Solvent-1: High-purity isohexane (manufactured by Sankyo Chemical Co., Ltd.) Solvent-2: Marukasol FH (cyclopentane, manufactured by Maruzen Petrochemical Co., Ltd.) Solvent-3: Methylcyclohexane (manufactured by Sankyo Chemical Co., Ltd.)

[0036] <Surfactant> Surfactant-1: Antigel 6217 (surfactant, manufactured by Brend Schewegmann GmbH & Co. KG (Germany)) Surfactant-2: DISPERBYK-102 (surfactant, manufactured by BYK-Chemie, Germany) Surfactant-3: SCHWEGO wett 6292 (surfactant, manufactured by Brend Schewegmann GmbH & Co. KG (Germany)) Surfactant-4: DISPERBYK-108 (surfactant, manufactured by BYK-Chemie, Germany) Surfactant-5: Disparlon PW-36 (surfactant, manufactured by Kusumoto Chemicals Co., Ltd.) Surfactant-6: Homogenol L-18 (surfactant, manufactured by Kao Corporation) Surfactant-7: Prophane (surfactant, manufactured by Sanyo Chemical Industries, Ltd.)

[0037] <Fruit silica, fatty acid amide, modified urea, oxidized polyethylene, bentonite> Dry silica-1: Aerosil R972 (hydrophobic dry silica, manufactured by Nippon Aerosil Co., Ltd.) Dry silica-2: Aerosil 200 (Dry silica, manufactured by Nippon Aerosil Co., Ltd.) Dry silica-3: Aerosil RX200 (hydrophobic dry silica, manufactured by Nippon Aerosil Co., Ltd.) Dry silica-4: Aerosil 50 (Dry silica, manufactured by Nippon Aerosil Co., Ltd.) Dry silica-5: Aerosil 380 (Dry silica, manufactured by Nippon Aerosil Co., Ltd.) Dry silica-6: Aerosil R976-S (hydrophobic dry silica, manufactured by Nippon Aerosil Co., Ltd.) Fatty acid AM-1: Disparlon 6820-20M (fatty acid amide, 20% active ingredient, manufactured by Kusumoto Chemicals Co., Ltd.) Modified urea-1: BYK-411 (modified urea, 27% active ingredient, manufactured by BYK-Chemie (Germany)) Oxidized PE-1: PF-920 (Oxidized polyethylene, 20% active ingredient, manufactured by Kusumoto Chemicals Co., Ltd.) Bentonite-1: Esben N-400 (organic bentonite, manufactured by Hojun Co., Ltd.)

[0038] <Particles with a major axis of 1.6 μm to 170 μm, a minor axis of 0.1 μm to 1.3 μm, and an aspect ratio (major axis / minor axis) of 5 or more> Particle-1: Whiscal A (calcium carbonate, major axis 20 μm, minor axis 1 μm, aspect ratio 20.0, specific gravity 2.86, manufactured by Maruo Calcium Co., Ltd.) Particle-2: FTL-300 (titanium oxide, major axis 5.15 μm, minor axis 0.27 μm, aspect ratio 19.1, specific gravity 4.2, manufactured by Ishihara Sangyo Kaisha, Ltd.) Particle-3: Silar (silicon carbide, major axis 40 μm, minor axis 0.55 μm, aspect ratio 72.7, specific gravity 3.2, manufactured by Haydale Technologies Inc. (UK)) Particle-4: FTL-100 (major axis 1.68 μm, minor axis 0.13 μm, aspect ratio 12.9, specific gravity 4.2, manufactured by Ishihara Sangyo Kaisha, Ltd.) Particle-5: FTL-200 (major axis 2.86 μm, minor axis 0.21 μm, aspect ratio 13.6, specific gravity 4.2, manufactured by Ishihara Sangyo Kaisha, Ltd.) Particle-6: Silicon nitride whisker (long diameter 170 μm, short diameter 1.3 μm, aspect ratio 130.7, specific gravity 3.18, Tateho Chemical Industries Co., Ltd.) Particle-7: Particles (calcium carbonate, major axis 10 μm, minor axis 1 μm, aspect ratio 10.0, specific gravity 2.86) obtained by crushing Whiskal A in a planetary ball mill (Planetary Ball Mill Quartet P-5, Fritsch, Germany) using φ10 mm beads at 150 rpm for 5 minutes. Particle-8: Particles (calcium carbonate, major axis 8 μm, minor axis 1 μm, aspect ratio 8.0, specific gravity 2.86) obtained by crushing Whiskal A in a planetary ball mill (Planetary Ball Mill Quartet P-5, Fritsch, Germany) using φ10 mm beads at 200 rpm for 5 minutes. Particle-9: Particles (calcium carbonate, major axis 5 μm, minor axis 1 μm, aspect ratio 5.0, specific gravity 2.86) obtained by crushing Whiskal A in a planetary ball mill (Planetary Ball Mill Quartet P-5, Fritsch, Germany) using φ10 mm beads at 250 rpm for 5 minutes.

[0039] <Particles with a major axis of 1.6 μm or more and 170 μm or less, a minor axis of 0.1 μm or more and 1.3 μm or less, and an aspect ratio (major axis / minor axis) of not more than 5> Particle-10: PANGEL-B5 (hydrated magnesium silicate, major axis 1.7 μm, minor axis 0.02 μm, aspect ratio 85.0, TOLSA (Spain)) Particle-11: NYAD-G (calcium silicate, major axis 825 μm, minor axis 55 μm, aspect ratio 15.0, IMERYS (USA)) Particle-12: NYAD 1250 (calcium silicate, major axis 12 μm, minor axis 4 μm, aspect ratio 3.0, IMERYS (USA)) Particle-13: Super S (heavy calcium carbonate, major axis 4 μm, minor axis 4 μm, aspect ratio 1.0, manufactured by Maruo Calcium Co., Ltd.) Particle-14: PC (light calcium carbonate, major axis 1.2 μm, minor axis 0.48 μm, aspect ratio 2.5, manufactured by Shiraishi Kogyo Co., Ltd.) In the present invention, the major axis and minor axis are values ​​calculated by the method of JIS Z 8827-1:2008, which is obtained by taking an image of a particle, measuring the maximum Feret diameter (maximum Feret diameter, the distance between two parallel lines when an image of a particle is sandwiched between two parallel lines) of 200 randomly selected particles as the major axis (L) and the minimum Feret diameter (minimum Feret diameter) as the minor axis (D), and calculating the values ​​according to the following formula. Major axis = Σ(Li 2 ) / ΣLi Minor axis = Σ(Di 2 ) / ΣDi Aspect ratio = L / D = [Σ(Li 2 ) / ΣL] / [Σ(Di 2 ) / ΣDi] (The major axis (particle size) of each particle was defined as L1, L2, ..., L200, and the minor axis was defined as D1, D2, ..., D200.)

[0040] <Pigments> Black pigment-1: Tilack D (low-order titanium oxide, black pigment, manufactured by Ako Kasei Co., Ltd.) Yellow pigment-1: Tarox LL-100 (yellow iron oxide, manufactured by Titanium Industries Co., Ltd.) Yellow pigment-2: PV FAST YELLOW H2G (CI Pigment Yellow 120, Clariant Chemicals Co., Ltd.) Green pigment-1: T-18N Signal Green (green fluorescent pigment, manufactured by DayGlo, USA) Blue pigment-1: PV FAST BLUE BG (CI Pigment Blue 15:3, Clariant Chemicals Co., Ltd.) Red pigment-1: Chromofine Red 6820 (CI Pigment Violet 19, Dainichi Seika Color & Chemicals Co., Ltd.) Orange pigment-1: PV FAST YELLOW H3R-LHC (CI Pigment Yellow 181, Clariant Chemicals Co., Ltd.) Extender pigment-1: Kyoward 700 (aluminum silicate, manufactured by Kyowa Chemical Industry Co., Ltd.)

[0041] Plasticizer-1: MAR-N (methyl acetyl ricinoleate, manufactured by Daihachi Chemical Co., Ltd.) Wet silica-1: P-603 (wet silica, Mizusawa Industrial Chemicals) Wet silica-2: P-801 (wet silica, Mizusawa Industrial Chemicals) Amino acid-1: GP-1 (dibutyl lauroyl glutamide, manufactured by Ajinomoto Co., Inc.)

[0042] The "weight ratio" shown in the table indicates the ratio by weight of the content of particles having a major axis of 1.6 μm or more and 170 μm or less, a minor axis of 0.1 μm or more and 1.3 μm or less, and an aspect ratio (major axis / minor axis) of 5 or more to a mixture of one or more types selected from dry silica, fatty acid amide, modified urea, polyethylene oxide, and bentonite, when the content of the mixture of one or more types selected from dry silica, fatty acid amide, modified urea, polyethylene oxide, and bentonite is taken as 1.

[0043] The "volume occupancy ratio" listed in the table indicates the volume occupancy ratio in the correction fluid of particles with a major axis of 1.6 μm or more and 170 μm or less, a minor axis of 0.1 μm or more and 1.3 μm or less, and an aspect ratio (major axis / minor axis) of 5 or more, to dry silica.

[0044] The "specific gravity difference" shown in the table indicates the difference in specific gravity between dry silica and calcium carbonate particles having a major axis of 1.6 μm or more and 170 μm or less, a minor axis of 0.1 μm or more and 1.3 μm or less, and an aspect ratio (major axis / minor axis) of 5 or more.

[0045] In order to evaluate the correction fluids according to the Examples and Comparative Examples, the applicator shown in FIG. 1 was created and filled with 7 mL of the correction fluids of Examples 1 to 41 and Comparative Examples 1 to 10 to prepare test applicators.

[0046] Visible hiding power: A straight line was drawn using a test applicator from the white area to the black area on a hiding rate measurement paper (based on JIS K 5600) to visually evaluate the hiding power of the coating film. If the coating film part on the white area and the coating film part on the black area are recognized to have different visual colors, it is evaluated as having no visible hiding power. The table below lists the results of the visible hiding power test under each condition and an explanation of the conditions. Initial visibility hiding power: Using a test applicator filled with correction fluid immediately after blending, a straight line was drawn from the white part to the black part of the hiding rate measurement paper to form a coating film, and the visibility hiding power of the coating film was evaluated by visual inspection. First visible hiding power: A cap was placed on the test applicator used to evaluate initial visible hiding power, and the test applicator was left to stand at room temperature for 6 months with the discharge port facing upwards. The test applicator was then shaken 5 times and then the cap was removed. A straight line was drawn across the white and black parts of the hiding rate measurement paper to form a coating film, and the visible hiding power of the coating film was evaluated by visual inspection. Second visible hiding power: A cap was placed on the test applicator used for evaluating the first visible hiding power, and the test applicator was left to stand again for 6 months at room temperature with the nozzle facing upwards. After that, the test applicator was shaken 5 times and then the cap was removed. A straight line was drawn across the white and black parts of the hiding rate measurement paper to form a coating film, and the visible hiding power of the coating film was evaluated by visual inspection. Third visible hiding power: A cap was placed on the test applicator used for evaluating the second visible hiding power, and the test applicator was left to stand again for 6 months at room temperature with the nozzle facing upwards. After that, the test applicator was shaken 5 times and then the cap was removed. A straight line was drawn across the white and black parts of the hiding rate measurement paper to form a coating film, and the visible hiding power of the coating film was evaluated by visual inspection. Visibility Concealment Rating Criteria: ◯: No visible difference in color between the coating film part on the white part and the coating film part on the black part. ×: A difference in color between the coating film part on the white part and the coating film part on the black part is visually recognized.

[0047] (Concealment rate test) The correction fluid obtained in each Example and Comparative Example was applied to a hiding rate measurement paper (JIS K 5600, a paper in which a white part and a black part are printed adjacent to each other and a varnish is applied, which can be easily painted with a paint diluted with a solvent or water but does not penetrate) with a 50 μm applicator, and after drying, the Y values ​​of the coating film in the white part and the coating film in the black part of the hiding rate measurement paper were measured with a color computer (SE6000, manufactured by Nippon Denshoku Kogyo Co., Ltd.), and the ratio (Y value of the coating film in the black part / Y value of the coating film in the white part) was calculated as a percentage to obtain the hiding rate. The closer the hiding rate is to 100%, the higher the hiding power is, and if it is less than 90%, the hiding power is insufficient and the color underneath the coating film is visible. The notation of the hiding rate test results in the table under each condition and the explanation of the conditions are described below. Initial hiding rate (%): Immediately after preparation of the correction fluid, the hiding rate was measured by the above hiding rate test. First-time hiding rate (%): The cap was placed on the test applicator, and after leaving it at room temperature for 6 months with the nozzle facing upwards, the test applicator was shaken 5 times and then the front barrel was removed, the correction fluid was removed, and the hiding rate was measured using the above-mentioned hiding rate test. Second concealment rate (%): The test applicator with the front barrel replaced immediately after removing the correction fluid in the measurement of the first concealment rate (%) was left standing again at room temperature for 6 months with the nozzle facing upwards, after which the test applicator was shaken 5 times, the front barrel was removed, the correction fluid was removed, and the concealment rate was measured using the above concealment rate test. 3rd Concealment Rate (%): Immediately after removing the correction fluid for the 2nd Concealment Rate (%) measurement, the test applicator with the front barrel replaced was left again at room temperature with the nozzle facing upwards for 6 months, after which the test applicator was shaken 5 times, the front barrel was removed, the correction fluid was removed, and the concealment rate was measured using the above concealment rate test. Rate of change in concealment rate: The rate of change between the initial concealment rate (%) and the third concealment rate (%) (third concealment rate / initial concealment rate) was calculated.

[0048] (Deformation load test) The correction fluid obtained in each Example and Comparative Example was poured into a screw-cap bottle S-5 (glass container, manufactured by Nichiden Rika Glass Co., Ltd., depth 70 mm, inner diameter 17 mm, capacity 12 mL) to a height of 50 mm, and a FUDOH rheometer RTC-3010D (rheometer, manufactured by Rheotec Co., Ltd.) was used to measure the load when an adapter with an outer diameter of 10 mm and a thickness of 1 mm was pushed into the correction fluid at a speed of 2 cm / min. The maximum load value up to the point where the depth of 49 mm from the liquid surface of the correction fluid was reached was taken as the deformation load, and was used as an index of the ease of deformation (fluidity) against external forces. When the adapter reaches the bottom of the bottle, the load pushing into the correction fluid is not detected and the value measured by the rheometer becomes maximum, so the detection was taken as up to 49 mm just before the adapter penetrates into the correction fluid and reaches the bottom of the bottle. It is considered that the smaller the deformation load value, the smaller the load required to push the adapter into the correction fluid at a constant speed, and it is considered that the adapter is more likely to deform against external forces and to exhibit a gentle and efficient stirring effect. The notation of the deformation load test results in the table for each condition and an explanation of the conditions are given below. First deformation load (g): The screw-cap bottle S-5 containing the prepared correction fluid was sealed with a lid and allowed to stand at room temperature for 6 months. The lid was then removed and the above deformation load test was carried out. Second deformation load (g): Immediately after measuring the first deformation load, the correction fluid was stirred with a spatula for 10 seconds, the container was sealed with a lid, and left to stand at room temperature for 6 months. The lid was then removed and the above deformation load test was conducted. Third deformation load (g): Immediately after measuring the second deformation load, the correction fluid was stirred with a spatula for 10 seconds, the container was sealed with a lid, and left to stand at room temperature for 6 months. The lid was then removed, and the above deformation load test was conducted.

[0049] [Table 1]

[0050] [Table 2]

[0051] [Table 3]

[0052]

Table 4

[0053]

Table 5

[0054]

Table 6

[0055]

Table 7

[0056]

Table 8

[0057]

Table 9

[0058]

Table 10

[0059] The correction fluids of Examples 1 to 41 are particles having a major axis of 1.6 μm to 170 μm, a minor axis of 0.1 μm to 1.3 μm, and an aspect ratio (major axis / minor axis) of 5 or more, and have hydroxyl groups on the surface, and are a mixture of one or more types selected from calcium carbonate, titanium oxide, and silicon nitride. Therefore, even after repeated stirring, application, and leaving to stand for a long period of time, the particles are discharged well, and a smooth, high-concealing, and good coating film is obtained. In particular, the correction fluids of Examples 1 to 13 and 30 to 41 have a weight ratio of particles having a major axis of 1.6 μm or more and 170 μm or less, a minor axis of 0.1 μm or more and 1.3 μm or less, and an aspect ratio (major axis / minor axis) of 5 or more to a mixture of one or more selected from dry silica, fatty acid amide, modified urea, polyethylene oxide, and bentonite of 5 or more and 1500 or less, so that the rate of change in hiding rate is approximately 1, the deformation load is also approximately constant between the first deformation load and the third deformation load, and even when stirring, application, and leaving to stand for a long period of time are repeated, a good coating film with a particularly high hiding rate is obtained. In addition, the correction fluids of Examples 1 to 13 are made of calcium carbonate particles with a major axis of 1.6 μm to 170 μm, a minor axis of 0.1 μm to 1.3 μm, and an aspect ratio (major axis / minor axis) of 5 or more, and the difference in specific gravity with dry silica is 0.7 or less. Therefore, even when the correction fluids are repeatedly stirred, applied, and left to stand for a long period of time, a good coating film with a particularly high hiding rate is obtained. Furthermore, in the correction fluids of Examples 1 to 13, the ratio of the volume occupancy of particles having a major axis of 1.6 μm or more and a minor axis of 0.1 μm or more and a minor axis of 1.3 μm or less, and an aspect ratio (major axis / minor axis) of 5 or more to dry silica is 3.8 or more and 1153.8 or less, so even when the correction fluids are repeatedly stirred, applied, and left to stand for a long period of time, a good coating film with a particularly high hiding rate is obtained.

[0060] In contrast, when the correction fluids of Comparative Examples 1 to 10 were evaluated for visibility and concealment after repeated stirring, application, and leaving to stand for a long period of time, only a thin liquid was discharged, resulting in a coating film with no visibility and concealment. The correction fluids of Comparative Examples 1 to 10 also had a third-time concealment rate significantly below 90%, and the black part of the concealment rate test paper underneath the coating was visible and not concealed, resulting in an unsatisfactory coating. [Explanation of symbols]

[0061] 1 Correction fluid 2 rear axle 3. Chip 3a Discharge port 3b Occlusion 4 Front axle 5. Coating 6 Applied body 6a Protrusion 6b Tip 6c base 7 Stirring body 8 Coil spring 9 Core body 9a Tip

Claims

1. The correction fluid contains at least titanium oxide, a hydrocarbon solvent, particles having a major axis of 1.6 μm or more and 170 μm or less, a minor axis of 0.1 μm or more and 1.3 μm or less, an aspect ratio (major axis / minor axis) of 5 or more, and having hydroxyl groups on the surface, and one or a mixture of two or more selected from dry silica, fatty acid amide, modified urea, polyethylene oxide, and bentonite.

2. The correction fluid described in claim 1, characterized in that the particles have a major axis of 1.6 μm or more and a minor axis of 0.1 μm or more and a minor axis of 1.3 μm or less, an aspect ratio (major axis / minor axis) of 5 or more, and the particles having hydroxyl groups on their surfaces are one or a mixture of two or more types selected from calcium carbonate, titanium oxide, and silicon nitride.

3. The correction fluid according to claim 1 or claim 2, characterized in that the major axis is 1.6 μm or more and 170 μm or less, the minor axis is 0.1 μm or more and 1.3 μm or less, the aspect ratio (major axis / minor axis) is 5 or more, and the weight ratio of the particles having hydroxyl groups on their surfaces to a mixture of one or more types selected from dry silica, fatty acid amide, modified urea, polyethylene oxide, and bentonite is 5 or more and 1,500 or less.

4. A correction fluid containing at least titanium oxide, a hydrocarbon solvent, particles having a major axis of 1.6 μm to 170 μm, a minor axis of 0.1 μm to 1.3 μm, and an aspect ratio (major axis / minor axis) of 5 or more, and dry silica, wherein the particles having a major axis of 1.6 μm to 170 μm, a minor axis of 0.1 μm to 1.3 μm, and an aspect ratio (major axis / minor axis) of 5 or more are calcium carbonate, and the difference in specific gravity between the particles and the dry silica is 0.7 or less.

Citation Information

Patent Citations

  • Coating method

    JP1988075073A

  • Cover-up liquid

    JP2001152097A

  • Oil-based gel ink composition and coating device using the ink composition

    JP2006206738A

  • Oily white ink

    JP2012131927A